Association between type of health insurance and dental visits among Ecuadorian older population: evidence from a cross-sectional study - Marite Falquez; Adriana Canessa-Rojas; Antonio Lanata-Flores; Freddy Espinoza-Carrasco; Ivan Cherrez-Ojeda; Karla Robles-Velasco; Marco Faytong-Haro; Claudia Reytor-González; Daniel Simancas-Racines (BMC Public Health)
Abstract Background Dental services are often overlooked within healthcare systems, despite their critical role in overall health. Socioeconomic barriers and disparities in insurance coverage frequently limit access to oral care, particularly among vulnerable populations like older adults. Objective To examine the impact of different health insurance types on the frequency of dental consultations among Ecuadorian senior citizens, aiming to highlight gaps in access to care. Methods Using the 2009 National Survey of Health, Well-being, and Aging (SABE), which aims to determine the health and living conditions of older individuals, this study analyzed the health insurance status and dental service visits of 4,565 older adults in Ecuador. Binary logistic regression was employed to explore the association between insurance type and dental-care utilization. Results In the sample, 76.50% of older adults had not visited a dentist in the past year. Insurance breakdown revealed 17.04% with general IESS, 9.59% with rural IESS, 2.23% with private insurance, 1.86% with ISSFA/ISSPOL, 1.86% with municipal insurance, and 69.66% were uninsured. Individuals with private insurance or ISSFA/ISSPOL insurance were 32% and 91% more likely, respectively, to seek oral care compared to those without these respective insurances. Conversely, uninsured individuals were 43% less likely to seek dental care than those with any type of insurance. Conclusion Health insurance significantly influences the frequency of dental consultations among Ecuadorian seniors, highlighting the need for policy interventions to ensure equitable access to oral care.